Residual hip dysplasia at 1 year after treatment for neonatal hip instability is not related to degenerative joint disease in young adulthood: a 21-year follow-up study including dGEMRIC. Issue 3 (March 2016) - Wenger, D.; Siversson, C.; Dahlberg, L.E.; Tiderius, C.J.
Summary: Objective: Developmental dysplasia of the hip (DDH) is associated with an increased risk of early hip osteoarthritis (OA). We aimed to examine the outcome at the completion of growth in a cohort of children who had residual acetabular dysplasia at age 1 year following early treatment for neonatal instability of the hip (NIH). Design: We examined 21 of 30 subjects who had been treated with the von Rosen splint neonatally for NIH and had residual acetabular dysplasia at age 1 year. Mean follow-up time was 21 years (range 17–24). Signs of OA and acetabular dysplasia were assessed by radiography. Cartilage quality was assessed by delayed Gadolinium Enhanced Magnetic Resonance Imaging of Cartilage (dGEMRIC), a tool for molecular imaging of cartilage quality, at 1.5 T. Patient reported outcome (PRO) was assessed by the 12-item WOMAC score. Results: No study participant had radiographic OA (defined as Kellgren–Lawrence grade ≥2) or minimum joint space width (JSW) ≤2 mm. The mean dGEMRIC index was 630 ms (95% CI: 600–666, range: 516–825) suggesting good cartilage quality. The mean 12-item WOMAC score was 1.2. Two of three radiographic measurements of DDH correlated positively to the dGEMRIC index. Conclusions: Children treated neonatally for NIH have good hip function and no signs of cartilage degeneration at 21-year follow-up, despite residual dysplasia at age 1 year. Unexpectedly, radiographic signs of dysplasia were associated with better cartilage quality, as assessed with dGEMRIC. This may indicate cartilage adaptation to increased mechanical stress in mild hip dysplasia.